Letter to Richard Ohmann & His Reply - Ohmann, Richard; Yelin, Louise; O'Malley, Susan; Leder, Sharon; Jansen, Reamy (Radical Teacher, 2022)
I appreciate your questions, and the criticism they carry. It must be rare for someone who writes a political book (English in America: A Radical View of the Profession) to have a chance to discuss its argument and reception with those who share its aims, and whose criticism comes out of comradeship and struggle rather than the wish to score debating points or advance a career or defend a position. I'll try to reply in the same spirit.